Neurofibromatosis : reporte de un caso (2010)
ABSTRACT: Type I Neurofibromatosis (NF1) is an autosomal dominant disease that presents with multiple cutaneous lesions, named neurofibromas. Oral manifestations have been reported in low percentages, but the tongue has been the most common site. This is a report of a case of a young girl with neurofibroma which invaded the oral cavity and tongue and was treated at the Oral and Maxillofacial Surgery Service of Hospital Universitario San Vicente de Paúl.